Simplify the expression

(m2 ­- 5)(2m2 + 3)

2m4 ­- 13m ­- 15

-11m4 – 15

2m4 – 7m2 ­- 15 answer

-5m4 – 15

============================================

Simplify the expression.

a3(4a – 6b + 8ab4 )

2a3 – 3a3b + 4a3b4

2a4 – 3a3b + 4a4b4 answer

8a4b4

8a4 – 12a3b + 16a4b4

=====================================

Simplify the expression.

(10×2 ­- 3xy + 4y2) ­- (3×2 + 5xy)

7×2 + 2xy + 4y2 answer

7×2 – 8xy + 4y2

7×2 – 8xy – 4y2

5x2y2

=====================================

Simplify the expression.

(4×2 ­- 3y2 + 5xy) ­- (8xy + 3y2)

12x2y + 5xy

-4x2y + 5xy

4×2 – 3xy answer

4×2 – 6y2 – 3xy

=================================

Simplify the expression.

(5y + 3y2) + (-8y – 6y2)

3y + 3y2

-3y – 3y2 answer

13y + 9y2

22y3

——————————————

Simplify the expression.

(3×2 – x + 2) + (x2 +4x – 9)

4×2 + 3x – 7 answer

4×2 ­- 5x + 11

7×6 – 7

4×4 + 3×2 – 7

===============================

Find the degree of the polynomial expression shown below.

2a + 6b

6

2

0

=============================

Find the degree of the polynomial expression shown below.

5x2y4 + x